The effectiveness and associated factors of online psychotherapy on COVID-19 related distress: A systematic review and meta-analysis - Chi, Danni; Zhang, Yuanyuan; Zhou, Dongsheng; Xu, Guozhang; Bian, Guolin (Frontiers in Psychology, 2022)
Objective: A quantitative synthesis of online psychotherapies’ effectiveness in managing COVID-19 related distress is lacking. This study aimed to estimate online psychological interventions’ effectiveness and associated factors on COVID-19 related psychological distress. Methods: Multi-databases including PubMed, EBSCO, ProQuest, and Cochrane were searched repeatedly till the end of June 2022. Hand-picking was also utilized for relevant papers. Depression, anxiety, stress, and quality of sleep were evaluated as outcomes. The risk of bias was evaluated using the Cochrane tool. Data analyses were conducted through Review Manager (version 5.4.1). Results: A total of 13 studies involving 1897 participants were included for meta-analysis. Results showed that online psychotherapy significantly reduced the levels of depression (standard mean difference, SMD = -.45, 95% CI [-.69, -.20]), anxiety (SMD = -.67, 95% CI [-.99, -.36]), and stress (SMD = -.73, 95% CI [-1.11, -.34]), but not quality of sleep (SMD = -.53, 95% CI [-1.23, .17]). In addition, guided therapies were more effective than self-help ones on reducing levels of anxiety (2 = 5.58, p = .02, and I2 = 82.1%), and ≤ 2 weeks’ daily interventions were more effective on treating depression than 2-month weekly interventions (2 = 7.97, p = .005, I2 = 87.5%). Conclusion: Online psychological interventions effectively reduced COVID-19 related depression, anxiety, and stress levels, and the effectiveness was influenced by settings like guidance and duration and frequency.